Nanoliposomal system for augmented antibacterial and antiproliferative efficacy of Melissa officinalis L. extract - Nizam, Nagihan; Taner, Gokce; Cagal, Munevver Muge (Oxford Univ Press, 2024)
Objective This study focused on the nanoliposomal encapsulation of bioactive compounds extracted from Melissa officinalis L. (ME) using ethanol as a strategy to improve the antibacterial activity, anticytotoxic, and antiproliferative properties.Methods Nanoliposomes loaded with ME (MEL) were characterized for total phenolic content, particle size, polydispersity, and encapsulation efficiency. The minimum inhibitory concentration (MIC) values for MEL and ME were determined to evaluate antibacterial activity. To examine the toxicity profiles of ME and MEL, tests were conducted on the A549 and BEAS-2B cell lines using the MTT assay. Furthermore, an in vitro sctrach assay was conducted to evaluate the antiproliferative effects of ME and MEL on A549 cells.Results Nanoliposomes presented entrapment efficiency higher than 80%, nanometric particle size, and narrow polydispersity. The MIC values for MEL and ME were observed as 93.75 mu g/mu L against E. coli. MIC values for MEL and ME were achieved as 4.68 mu g/mu L and 9.375 mu g/mL against S. aureus, respectively. The IC50 values for ME were determined to be 1.13 mg/mL and 0.806 mg/mL, while the IC50 values for MEL were found to be 3.5 mg/mL and 0.868 mg/mL on A549 and BEAS-2B cell lines, respectively. Additionally, The MEL showed an antiproliferative effect against A549 cells at 500 mu g/mL concentration.Conclusion All experimental findings unequivocally demonstrate that the novel nanoliposomal system has effectively augmented the antibacterial activities and antiproliferative effects of ME. The initial findings indicate that nanoliposomes could effectively serve as carriers for ME in pharmaceutical applications.
Keywords: Lemon balm; Nanoliposome; Antiproliferative; Cytotoxic; Antibacterial